Localization schemes in Underwater Sensor Network (UWSN): A Survey - Mukhtiar Ahmed; Mazleena Salleh (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Underwater Wireless Sensor Networks (UWSNs) is much more attractive area for the researchers due to its versatile applications like tactical surveillance, assisted navigation, equipment monitoring, oceanography data collection, pollution monitoring, offshore exploration, disaster prevention and seismic monitoring. The researchers are also collecting the scientific data from underwater environment for observing mission. Due to the continuous node movement in underwater environment creates the majority of the problems for localization. Localization is one of the major issues in underwater environment. This survey paper focuses the different valuable localization schemes which focus the open issues and challenges for researchers.